Impact of Intervention Program on Production Technologies of Horticultural Crops among Rural Women Assam, India - Das, Manju Dutta; Saikia, Poree (International Journal of Bio-resource and Stress Management, 2023)
Women play a vital role both in farm and household activities. There is some evidence that despite the contribution made by rural women in food security they are not being well served by the existing extension system. They are in urgent need of understanding and acquiring new knowledge and skills on cultivation of horticultural crops, so that they could contribute more effectively to the production process. The present study was conducted to identify the knowledge of rural women of Assam, India about scientifically validated existing production technologies and disseminate the same among themselves. A multi-stage purposive-cum-stratified random sampling design was followed covering 1,500 respondents for the present study. The study revealed that majority of the rural women had a very low level of knowledge in all the aspects of cultivation of horticultural crops namely nursery production, nutritional management, plant protection, followed by production practices of horticultural crops, seed production, land preparation and harvesting. Five trainings were organized for rural women on various aspects of production technologies of horticultural crops and this intervention helped in improving the knowledge which was observed through feedback received from post-training analysis after one month and participation in open forum discussion. The rural women were highly motivated to adopt improved production technologies in their field and interested to consider this area as one of the entrepreneurial activities of self-help group.